High-throughput single nucleotide polymorphism (SNP) identification and mapping in the sesame (Sesamum indicum L.) genome with genotyping by sequencing (GBS) analysis - Uncu, Ayse Ozgur; Frary, Anne; Karlovsky, Petr; Doganlar, Sami (Molecular breeding, 2016)
Sesame ( Sesamum indicum L. syn. Sesamum orientale L.) is considered to be the first oil seed crop known to man. Despite its versatile use as an oil seed and a leafy vegetable, sesame is a neglected crop and has not been a subject of molecular genetic research until the last decade. There is thus limited knowledge regarding genome-specific molecular markers that are indispensible for germplasm enhancement, gene identification, and marker-assisted breeding in sesame. In this study, we employed a genotyping by sequencing (GBS) approach to a sesame recombinant inbred line (RIL) population for high-throughput single nucleotide polymorphism (SNP) identification and genotyping. A total of 15,521 SNPs were identified with 14,786 SNPs (95.26 %) located along sesame genome assembly pseudomolecules. By incorporating sesame-specific simple sequence repeat (SSR) markers developed in our previous work, 230.73 megabases (99 %) of sequence from the genome assembly were saturated with markers. This large number of markers will be available for sesame geneticists as a resource for candidate polymorphisms located along the physical chromosomes of sesame. Defining SNP loci in genome assembly sequences provides the flexibility to utilize any genotyping strategy to survey any sesame population. SNPs selected through a high stringency filtering protocol (770 SNPs) for improved map accuracy were used in conjunction with SSR markers (50 SSRs) in linkage analysis, resulting in 13 linkage groups that encompass a total genetic distance of 914 cM with 432 markers (420 SNPs, 12 SSRs). The genetic linkage map constitutes the basis for future work that will involve quantitative trait locus (QTL) analyses of metabolic and agronomic traits in the segregating RIL population.